Analysis of Students’ Self-Efficacy in Solving Mathematical Problem through Problem Based Learning - Rohantizani Rohantizani; Nuraina Nuraina; Mursalin Mursalin; Rahmi Hayati (Electronic Journal of Education, Social Economics and Technology, 2025)
Students with good self-efficacy are generally able to overcome challenges in various aspects of life. This study aimed to measure students’ self-efficacy in learning mathematics in the Mathematics Education Department of Malikussaleh University during the 2024/2025 academic year. With technological support, PBL can be implemented more interactively and flexibly, enabling students to access learning resources, engage in online discussions, and develop problem-solving abilities independently. A qualitative research method was employed, with data collected through a questionnaire. The subjects of this study were students enrolled in the Mathematics Education Department at Malikussaleh University. The data analysis in this study was carried out through three stages: data reduction, data display, and conclusion drawing. A total of 41 students participated in the study. The results showed that 6 students (15%) had high self-efficacy, 31 students (75%) had moderate self-efficacy, and 4 students (10%) had low self-efficacy. The average self-efficacy score among students was 76.47%.  Based on these findings, students of the Mathematics Education Department at Malikussaleh University can generally be categorized as having a moderate level of self-efficacy. Analysis of the questionnaire data indicates that most students put significant effort into solving the problems assigned by lecturers, and some reported never procrastinating on tasks. While some students disagreed with completing tasks only at the deadline, others disagreed with the idea of never postponing tasks and stated that they preferred to work under deadline pressure.  Strengthening this psychological construct is crucial not only for deepening students' understanding of mathematical concepts but also for improving their preparedness and effectiveness as future mathematics teachers.